SAFETY AND EFFICACY OF CORONARY INTERVENTION THROUGH DISTAL TRANSRADIAL ACCESS IN SUBJECTS WITH LOW BODY MASS INDEX - MAHMOOD, K; BASHIR, M; RAMZAN, M; ADEEB, O (Biological and Clinical Sciences Research Journal, 2023)
This study evaluated the efficacy and safety of coronary intervention through dTRA in subjects with low body mass index. The retrospective study was conducted in the Cardiology Department of Ch Pervaiz Elahi Institute of Cardiology Multan from January 2022 to January 2023. A total of 37 patients were included in the study. The patients were divided into Group A (cTRA, n=20) and Group B (dTRA, 17). Procedure-related information was recorded, including puncture time and success rate, procedural method and category, radiation exposure, compression hemostasis, and complications like degree of pain, hand swelling, numbness, hematoma, and bleeding. RAO was recorded in the follow-up. The puncture success rate in Group A was 97.5%, and in Group B was 96.7%; this difference was not statistically significant(P=.856). Group B had a longer puncture time than Group A (72s vs. the 60s, P=.003). 1 patient in group B had puncture failure and was switched to Group A. Procedural time in Group B was significantly longer than in Group A (46 min vs. 31 min, P=.043). Compression hemostasis time in Group B was significantly shorter than in Group A (5h vs. 7h, P<.001). The groups’ differences in post-operative complications, including hand swelling, numbness, hematoma, and bleeding, were not statistically significant. However, Group B had a significantly lower VAS score than Group A (1 vs. 2, P=<.001). Based on the results, Distal transradial access provides an effective and safe route for coronary intervention in subjects with low BMI.